On the Dislocation Properties of 60$^{°}$ Partial Dislocation in Silver: Core Structure and Peierls Stress (Journal of Atomic and Molecular Sciences, 2010)
Two-dimensional modified Peierls-Nabarro dislocation equationconcerning the discreteness of crystals is reduced toone-dimensional equation to determined the corestructure of partial dislocation in Ag. The generalized stackingfault energy along the Burgers vectors of partial dislocation is askewed sinusoidal force law, which is related to the intrinsicstacking fault energy and the unstable stacking fault energy. Atrial solution appropriate for arbitrary dislocation angle ispresented within the variational method. The results show that thehalf core width increases as the increase of dislocation angle.Moreover, the core width decreases with the increase of the unstablestacking fault energy and the intrinsic stacking fault energy.Peierls stress for $60^{°}$ partial dislocation is inagreement with the experimental results.
Keywords: core structure; partial dislocation; variational method; Peierls stress.